Hubungan Keaktifan Organisasi Dengan Rasa Percaya Diri Pada Mahasiswa - Go'o, Angeberta Avelenia; Geradus, Uda; Indrawan, Putu Agus (Prodi Bimbingan Konseling FKIP UNDANA, 2023)
This study aims to determine (1) the picture of the activeness of the FKIP Undana student organization, (2) the picture of the confidence of FKIP Undana students and (3) whether there is a relationship between organizational activity and self-confidence in students of the Faculty of Teacher Training and Education, Nusa Cendana University. This study used a quantitative approach with a correlation type of research. The research was conducted at Campus B FKIP Undana with an affordable population of 105 people and a sample of 63 respondents. The sampling technique is carried out by the simple random sampling method. Data collection technique using Likert scale questionnaire. The data analysis techniques used are descriptive analysis and product moment correlation analysis with the help of the SPPS program version 20. The results showed that organizational activity in FKIP Undana students was in the active category with a percentage of 52.4%, and the results of data analysis of the confidence of FKIP Undana students were in the confidence category with a percentage of 51%. Based on the correlation analysis of product moment, a sig value is obtained. (2-tailed) 0.000 and r-calculated value 0.797 at level 0.05 so r-table 0.2480. This shows that there is a strong/high positive relationship between organizational activity and self-confidence in students of the Faculty of Teacher Training and Education, Nusa Cendana University. The results of the product moment correlation test show that there is a high/strong relationship between organizational activity and the confidence of FKIP Undana students, and having a positive relationship means that high/strong levels of organizational activity can increase self-confidence. Based on the results of these findings, it can motivate students who are oragnized to continue to actively participate in every activity carried out by the organization and for students who have not organized, if you want to increase self-confidence, it can be done by joining and being active in organizational activities.